The Influence of Green Brand Image, Green Perceived Value, and Green Product Quality on Customer Loyalty in Users of The Body Shop Products - Medianti, Putu Devanie; Hussein, Ananda Sabil (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
This research aims to identify the effects of green brand image, green perceived value, and green product quality on customer loyalty among the consumers of The Body Shop in Malang City. This quantitative explanatory research explains the causal relationship between its variables through hypothesis testing. From the population of The Body Shop’s consumers in Malang City, 202 people were selected as the respondents using purposive sampling techniques. They are people with the minimum age of seventeen years who are currently using or who have purchased products from The Body Shop more than twice. The instruments of this research were assessed using validity tests, reliability tests, and classical assumption tests; while the data was analyzed through multiple linear regression, and the hypothesis testing was conducted using the F-test and t-test. All of the statistical analyses were performed in SPSS 25.0. This research finds that green brand image, green perceived value, and green product quality have a significant positive influence on the loyalty of the consumers of The Body Shop in Malang City.